INTEGRATED POLICY MANAGEMENT OF NARCOTICS TRAFFICKING AS TRANSNATIONAL ORGANIZED CRIME IN INDONESIA - Joko Setiyono (Fakultas Hukum, Universitas Diponegoro, 2020)
Indonesia is the closest state to the Southeast Asian Golden Triangle which is Asia's largest source of opium. Since 1990 until now, Indonesia has become marketing drugs for existence. The indicator of narcotics could be categorized as transnational crimes because of their internal factors and external factors, including drug abuse to the misuses authority by state officials to oversee on narcotics. As a sovereign state, Indonesia has policies in dealing with drug trafficking including transnational organized crime. One of them is by strengthening the performance of the National Narcotics Board of Correctional Institutions in combating narcotics in Indonesia.